Peranan Pendidikan dalam Menghadapi Berbagai Isu Strategis Pembangunan di Indonesia - Hasan, Helmi (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2006)
The strategic issues faced by Indonesian people include national disintegration and democratization, free-market, democratic economy, and the enchancing of educational quality. This paper will analyze the role of education in facing those issues. The analysis begins from the phenomena existed all this time; and try to anticipate the spread of the national problem. It seemed that all this time, the solving of this problem tended to give less attention to educational aspect, while it was very important and essential to solve this problem. Therefore, we should make any revolution in educational world, have high commitment to and be consistent with the rule as stated in our constitution, Undang-undang Dasar l945, that still far from the good implementation. Kata kunci: Mutu Pendidikan, Isu Strategis, Disintegrasi, Demokratisasi, Ekonomi Kerakyatan